Il c.d. aliunde perceptum: tra passato e presente - Di Maria, Sabrina (Cultura giuridica e diritto vivente, 2020)
[The so-called aliunde perceptum: between paste and present] The essay explores the relation between the italian labour law’s principle of aliunde perceptum and the texts of the Roman law and the Civilian tradition on the subject of locatio operarum.